Transiently elevated plasma methionine, S‐adenosylmethionine and S‐adenosylhomocysteine: Unreported laboratory findings in a patient with NGLY1 deficiency, a congenital disorder of deglycosylation. Issue 1 (22nd July 2019) - Chang, Caitlin A.; Wei, Xing‐Chang; Martin, Steven R.; Sinasac, David S.; Al‐Hertani, Walla
Abstract: We report on a 5‐year‐old female born to consanguineous parents, ascertained at the age of 23 months for an elevated plasma methionine level, a mildly abnormal total plasma homocysteine (tHcy), and elevated aminotransferases. She had global developmental delay, microcephaly, dysmorphic facial features, hypotonia, nystagmus and tremor in her upper extremities. Metabolic investigations demonstrated elevations in plasma methionine, plasma S ‐adenosylmethionine (SAM) and plasma S ‐adenosylhomocysteine (SAH), with normal urine adenosine levels. Some of the elevations persisted for over 1 year. Sequencing of the ADK and AHCY genes was negative for causative variants. Plasma methionine normalized 1 year after ascertainment, but SAM and SAH continued to be elevated for six more months before normalization, and aminotransferases remained mildly elevated. Whole exome sequencing demonstrated a homozygous pathogenic variant; NM_018297.3(NGLY1):c.1405C>T (p.Arg469*) in exon 9 of the NGLY1 gene, for which both parents were heterozygous. To our knowledge, this is the first report of NGLY1 deficiency with elevations in plasma methionine, SAM and SAH and a slight elevation of tHcy. Less than 20 patients have been reported with NGLY1 deficiency worldwide and this case expands on the biochemical phenotype of this newly discovered inborn error of metabolism.